2014
DOI: 10.2134/agronj14.0186
|View full text |Cite
|
Sign up to set email alerts
|

Crop Water Productivity of Sugarbeet as Affected by Tillage

Abstract: One of today's greatest challenges of irrigated agriculture is to produce more food and fiber with less water, which can be accomplished by maximizing crop water productivity (CWP). A study was conducted to evaluate and compare the effect of conventional tillage (CT) and strip tillage (ST) on crop water use (CWU) and CWP of sugarbeet (Beta vulgaris L.) on clay loam soil in the northern Great Plains (NGP). Seasonal CWU and CWP for sugarbeet root and sucrose yields were determined for the 2006, 2007, and 2008 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Dense soil surface layers commonly found on no-tillage managed fields can adversely affect establishment due to a low emergence force (Koch, 2009), although literature in this area is sparse. Strip tillage procedures are used for partial or complete removal of the soil surface layer by tilling narrow strips to control erosion (for both wind and water), reduce evaporation and avoid loss of soil organic matter (Jabro et al ., 2014). Similar yields for sugar beet have been reported compared with intensive tillage.…”
Section: Cultivation and Management Techniquesmentioning
confidence: 99%
“…Dense soil surface layers commonly found on no-tillage managed fields can adversely affect establishment due to a low emergence force (Koch, 2009), although literature in this area is sparse. Strip tillage procedures are used for partial or complete removal of the soil surface layer by tilling narrow strips to control erosion (for both wind and water), reduce evaporation and avoid loss of soil organic matter (Jabro et al ., 2014). Similar yields for sugar beet have been reported compared with intensive tillage.…”
Section: Cultivation and Management Techniquesmentioning
confidence: 99%
“…A similar relationship was not observed among interaction means for harvest population or sucrose concentration suggesting that root size is the yield component responsible for the interaction for sucrose yield. Jabro et al (2014) reported that, as a result of observed differences in root and adjusted sucrose yield, the ST system required 0.0093m 3 and 0.061m 3 less irrigation water than the CT system to produce 1 kg of sugarbeet root and 1 kg of sucrose yield, respectively, under MESA irrigation management.…”
Section: Results and Discussion Growing Conditionsmentioning
confidence: 99%
“…ST has a special enhancing effect on water in soil [13]. According to Jabro et al [14], the crop water productivity for sugar beet ST technology was 10% higher than for CT technology. Hasan et al [15] and Alhajj Ali et al [16] recommend simplified soil tillage methods also for wheat production, including zero tillage and ST, due to the highest water productivity and least total water used.…”
Section: Introductionmentioning
confidence: 99%